2013
DOI: 10.1111/1467-8578.12041
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of teachers' awareness and knowledge of (Central) Auditory Processing Disorder ((C)APD)

Abstract: The aim of this study was to explore primary school teachers' awareness and knowledge of (Central) Auditory Processing Disorder ((C)APD). Teachers' awareness and knowledge are crucial for initial recognition and appropriate referral of children suspected of having (C)APD. When a child is diagnosed with (C)APD, teachers have a role in implementing and monitoring the effectiveness of interventions. A questionnaire was designed and distributed to 53 primary schools in the Republic of Ireland. Findings indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Poor awareness and understanding of APD were reported by the majority of respondents of the present survey, particularly in professionals in relevant positions, in line with previous reports by surveyed professionals ( 41 43 ). This lack of knowledge among medical professionals is of concern, as it may lead to delayed diagnosis and management of APD in affected individuals, and failure to meet the guidelines of the National Service Framework (NSF) for “early recognition, prompt diagnosis, and treatment” ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Poor awareness and understanding of APD were reported by the majority of respondents of the present survey, particularly in professionals in relevant positions, in line with previous reports by surveyed professionals ( 41 43 ). This lack of knowledge among medical professionals is of concern, as it may lead to delayed diagnosis and management of APD in affected individuals, and failure to meet the guidelines of the National Service Framework (NSF) for “early recognition, prompt diagnosis, and treatment” ( 48 ).…”
Section: Discussionsupporting
confidence: 91%
“…RMHAs improve listening and attention skills in children ( 8 ), and adults with neurological-type APD ( 4 , 38 , 39 ), and are thus a reasonable adjustment as per the Equality Act 2010 ( 49 ). Our results highlight the need for teachers, in particular, to be better informed about APD ( 41 , 43 ) not least because they may be the first to notice gaps in a child's language, social behavior, and communication skills ( 25 ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In line with these results, it is suggested that an update to the curriculum with a dedicated course covering the most common and critical disorders and difficulties among school-age children, may be a useful strategy for all studentteachers in general and special education programs. Besides educators, several studies evaluated CAPD awareness among audiologists and speech pathologists (Hind, 2006;Baldry & Hind, 2008;Logue-Kennedy et al, 2011), reaching a similar conclusion of limited familiarity and professional readiness Given the limited but consistent evidence on the lack of CAPD awareness and preparedness among those concerned (Hlabangwane, 2002;Ryan & Logue-Kennedy, 2013;Fletcher, 2017), a potential line of investigation to further delineate the extent of the problem includes general education teachers and their knowledge of causes, symptoms, and characteristics of CAPD, as well as their their ability to distinguish the disorder from other conditions and effectively refer or intervene when required (Almusawi et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…A later study by Ryan and Logue-Kennedy (2013) explored the levels of CAPD awareness amongst mainstream primary school teachers in the Republic of Ireland. Eighty-nine percent (89%) of respondents reported 'very poor' levels of awareness.…”
Section: Introductionmentioning
confidence: 99%